Hydroquinone–pyrrole dyads with varied linkers - Huang, Hao; Karlsson, Christoffer; Strømme, Maria; Sjödin, Martin; Gogoll, Adolf (Beilstein Journal of Organic Chemistry, 2016)
A series of pyrroles functionalized in the 3-position with p-dimethoxybenzene via various linkers (CH2, CH2CH2, CH=CH, C≡C) has been synthesized. Their electronic properties have been deduced from 1H NMR, 13C NMR, and UV–vis spectra to detect possible interactions between the two aromatic subunits. The extent of conjugation between the subunits is largely controlled by the nature of the linker, with the largest conjugation found with the trans-ethene linker and the weakest with the aliphatic linkers. DFT calculations revealed substantial changes in the HOMO–LUMO gap that correlated with the extent of conjugation found experimentally. The results of this work are expected to open up for use of the investigated compounds as components of redox-active materials in sustainable, organic electrical energy storage devices.
Keywords: conjugation; heterocycles; hydroquinone; linker effect; pyrrole